Correlation of the Apparent Diffusion Coefficient (ADC) with the Standardized Uptake Value (SUV) in Hybrid 18F-FDG PET/MRI in Non-Small Cell Lung Cancer (NSCLC) Lesions: Initial Results - Heusch, P.; Buchbender, C.; Köhler, J.; Nensa, F.; Beiderwellen, K.; Kühl, H.; Lanzman, R. S.; Wittsack, H. J.; Gomez, B.; Gauler, T.; Schuler, M.; Forsting, M.; Bockisch, A.; Antoch, G.; Heusner, T. A. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2013)
Purpose: To compare the apparent diffusion coefficient (ADC) in non-small cell lung cancer lesions with standardized uptake values (SUV) derived from combined 18F-fluoro-deoxy-glucose-positron emission tomography/magnetic resonance imaging (FDG-PET/MRI) and those derived from FDG-PET/CT.Materials and Methods: In 18 consecutive patients with histologically proven NSCLC (17 men, 1 woman; mean age, 61 ± 12 years), whole-body FDG-PET/MRI was performed after whole-body FDG-PET/CT. Regions of interest (ROI) encompassing the entire primary tumor were drawn into FDG-PET/CT and FDG-PET/MR images to determine the maximum and mean standardized uptake value (SUVmax; SUVmean) and into ADC parameter maps to assess mean ADC values. Pearson’s correlation coefficients were calculated to compare SUV and ADC values.Results: The SUVmax of NSCLC was 12.3 ± 4.8 [mean ±SD], and the SUVmean was 7.2 ± 2.8 as assessed by FDG-PET/MRI. The SUVmax and SUVmean derived from FDG-PET/CT and FDG-PET/MRI correlated well (R = 0.93; p < 0.001 and R = 0.92; p < 0.001, respectively). The ADCmean of the pulmonary tumors was 187.9 ± 88.8 × 10–5 mm²/s [mean ± SD]. The ADCmean exhibited a significant inverse correlation with the SUVmax (R = –0.72; p < 0.001) as well as with the SUVmean assessed by FDG-PET/MRI (R = –0.71; p < 0.001).Conclusion: This simultaneous PET/MRI study corroborates the assumed significant inverse correlation between increased metabolic activity on FDG-PET and restricted diffusion on DWI in NSCLC.Citation Format:
Keywords: thorax; MR diffusion/perfusion; PET-CT